Platelet Rich Fibrin in Socket Preservation - Monalisha Mohapatra (Indian Journal of Forensic Medicine & Toxicology, 2020)
With the advancement in dentistry, there are different ways of treatment such as restoration, surgicalprocedures as well as aesthetic treatments socket healing after extraction comprises of hard tissue as wellas soft tissue reconstruction with changes which is maximum dimensionally during the initial three months.One of the major challenges in clinical science is the development of bioactive surgical additives to improvethe pace of the process of healing and inflammation control. Platelet-rich fibrin (PRF) exists in this contextas a safe and adequate substitute with less risk and favourable outcomes. The methodology of use of PRF,concentration on its planning advantages and drawbacks of use in clinical applications are summarized inthe following review. Platelet-rich fibrin (PRF) was developed in France first as a beneficial substitute toplatelet-rich plasma to overcome its limitations